Urban sprawl, food security and agricultural systems in developing countries: A systematic review of the literature - Hatab, Assem Abu; Cavinato, Maria Eduarda Rigo; Lindemer, August; Lagerkvist, Carl Johan (Elsevier, 2019)
In developing countries, urbanisation and associated demographic changes pose unprecedented challenges in terms of hunger, food insecurity and malnutrition. A systematic review methodology was conducted, combined with data synthesis, to examine the interactions between urban sprawl, land and resource use changes, agricultural production and food security in developing countries. The Web of Science and Scopus databases were searched to identify 188 relevant articles. The results revealed that existing literature has widely failed to take interactions between different aspects of urban food systems (UFS) into account, indicating disconnects and fragmentation in the approaches used to analyse these interactions. Therefore a further focus on food system transformation pathways, system feedbacks and trade-offs is recommended. Moreover, the results imply that UFS are complex interlinked systems and therefore that policies intending to assure food security in developing countries need to consider these interlinkages and approach them holistically. Finally, an absence of studies examining urban and rural systems from an interconnected perspective was identified. An acknowledgement of such rural-urban connectivity gaps is crucial in order to ensure more inclusive links within food systems and agricultural value chains, and achieve more resilient food systems and more sustainable urbanisation in developing countries.